2021
DOI: 10.1007/s42761-021-00035-z
|View full text |Cite
|
Sign up to set email alerts
|

How the Affective Quality of Social Connections May Contribute to Public Health: Prosocial Tendencies Account for the Links Between Positivity Resonance and Behaviors that Reduce the Spread of COVID-19

Abstract: Although behaviors such as handwashing, mask wearing, and social distancing are known to limit viral spread, early in the COVID-19 pandemic, many individuals in the United States did not adopt them. The positivity resonance theory of coexperienced positive affect (Fredrickson, 2016) holds that shared pleasant states that include the key features of mutual care and a sense of oneness through behavioral synchrony function to build prosocial tendencies (e.g., self-transcendent and otheroriented dispositions of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…In a nationally representative sample, compassion for people with COVID-19 was associated with greater endorsement of government response measures to prevent transmission of the virus [13]. Another study looked at a latent construct referred to as "prosocial tendencies", which predicted health behaviors such as mask wearing [14]. A study that focused on empathy found that empathic concern, or a subset of empathy referring to feelings of concern for others in distress, was correlated with the belief that wearing a mask in public is the right thing to do [15].…”
Section: Compassion Empathy and Responses To The Pandemicmentioning
confidence: 99%
“…In a nationally representative sample, compassion for people with COVID-19 was associated with greater endorsement of government response measures to prevent transmission of the virus [13]. Another study looked at a latent construct referred to as "prosocial tendencies", which predicted health behaviors such as mask wearing [14]. A study that focused on empathy found that empathic concern, or a subset of empathy referring to feelings of concern for others in distress, was correlated with the belief that wearing a mask in public is the right thing to do [15].…”
Section: Compassion Empathy and Responses To The Pandemicmentioning
confidence: 99%
“…The first published empirical research on positivity resonance validated a new self-report measure of perceived positivity resonance and showed that it is associated, within individuals, with flourishing mental health, fewer depressive symptoms, loneliness, and (albeit less consistently) illness symptoms, even when controlling for daily pleasant emotions or amount of social interaction more generally (Major et al, 2018). More recent research that used this same measure of perceived positivity resonance during the early months of the coronavirus disease (COVID-19) pandemic found it to account for the link between trait resilience and mental health (Prinzing et al, 2020) and also to predict behaviors known to promote public health (i.e., handwashing, mask wearing, and social distancing), as mediated by prosocial tendencies (West et al, 2021). Here, we aim to advance this prior work by measuring positivity resonance through a suite of objective, dyad-level methods and in a social context (i.e., long-term marriage) to further illuminate its longitudinal consequences for health and longevity.…”
Section: Positivity Resonance Theory Of Coexperienced Positive Affectmentioning
confidence: 99%
“…Previously, the trio of collective responses was articulated as “(1) shared positive emotion, (2) mutual care, and (3) biobehavioral synchrony” (Fredrickson, 2016, p. 852). Our new phrasing decouples behavioral from biological synchrony to align better with the operationalized divisions among emotion response systems into experiential (i.e., shared positive-valence affect), behavioral (i.e., caring and synchronized nonverbal behaviors), and biological (i.e., physiological linkage) indicators, as has been done in recent articles (Brown & Fredrickson, 2021; Prinzing et al, 2020; West et al, 2021).…”
mentioning
confidence: 99%
“…A second theme relates to the role of individualism vs. collectivism in decision-making during COVID-19, with prior research indicating that some are motivated by protecting others (i.e., a sense of community responsibility), while others are primarily motivated by self-protection, in which case perceived personal susceptibility is a much more influential factor (Comfort et al, 2020;Burrai et al, 2021;Kumano et al, 2021;Lu et al, 2021;West et al, 2021). Third, there is clear evidence that health behaviors related to COVID-19 have become increasingly politicized, especially in the US (Byrd and Białek, 2021;Rabin and Dutra, 2021;Tan et al, 2021;Testa et al, 2021), with the implication that perceived benefits and barriers to taking action are driven largely by political affiliation and politically driven messaging.…”
Section: Introductionmentioning
confidence: 99%